Care Complexity Factors and Discharge Destination in an Emergency Department: A Retrospective Cohort Study - Urbina, Andrea; Adamuz, Jordi; Juvé-Udina, Maria-Eulàlia; Peñafiel-Muñoz, Judith; Munoa-Urruticoechea, Virginia; González-Samartino, Maribel; Delgado-Hito, Pilar; Jacob, Javier; Romero-García, Marta (Archives of Academic Emergency Medicine, 2025)
Introduction: Emergency department discharge destination is an important topic in both clinical practice and management. This study aimed to analyze the association of Care Complexity Individual Factors (CCIFs) with discharge destinations in patients who visit the emergency department (ED). Methods: This is a retrospective cohort study with consecutive sampling, including all patients who visited the ED of a tertiary hospital during 2021-2022. Data were collected from electronic health records. The main study outcomes were discharge destinations (mortality, intensive care unit admission, hospitalization, left without being seen/discharge against medical advice, and home discharge) and 26 CCIFs. Independent multinomial logistic regression was used for assessing the association of each factor and the discharge destinations, adjusted for age, sex, and triage level. All analyses were performed with R, version 4.3.2. Results: A total of 35,383 patients were included. Of these, 60.8% were home discharged, 34.1% were hospitalized, 2.6% were transferred to the intensive care unit, 2.1% were left without being seen, and 0.4% died. The presence of CCIFs was a risk factor of ED mortality (odds ratio (OR): 13.49 [95% confidence interval (CI): 4.99;36.46]), intensive care unit admission (OR:1.26 [95%CI:1.08;1.47]), and hospitalization (OR: 1.62 [95%CI:1.53;1.71]), whilst the presence of care complexity factors was a protective factor of discharge against medical advice (OR:0.64 [95%CI:0.55;0.74]). Conclusion: The discharge destinations from the ED showed strong associations with the patient’s complexity factors. Health professionals should consider these relationships for the design of early detection strategies and as an aid in decision-making, to ensure equity and quality of care.